Corporate social responsibility in the energy sector the role of stakeholders and Korea Electric Power Corporation-Salcon Power Corporation (KSPC) in the Visayas based-load power development project in Brgy. Colon, Naga City, Cebu - Agero, Nikki Rose L. (2013.)
This research study examines the roles and strategies utilized by the different stakeholders (i.e. Asian Development Bank, DOE, DENR-7, Municipal Government of Naga City, Cebu and Civil society Organizations) in promoting corporate social responsibility in the Visayas Base-Load Power Development Project owned by KSPC in Brgy. Colon, Naga City, Cebu from 2003 to the present. The paper also identifies and analyzes the interrelationships between the various actors/stakeholders. In the study, the resource relationship employed by ADB, DOE and DENR-7 towards KSPC was of high interdependence. The use of direct usage strategies was employed by stipulating terms and conditions to influence the KSPC's observance of corporate social responsibility in the coal-fired power plant. The relationship between the Municipality of Naga City, Cebu and KSPC exhibited firm power for the project was approved and endorsed by the national government under a Built-Own-Operate scheme. It is favorable to use indirect usage strategies such as sending letters/complaints to the responsible individuals in oder to exert pressure/demands to the company. Between the civil society organizations and KSPC, the resource relationship was marked by firm power and low interdependence. The civil society organizations utilized indirect withholdings/usage strategies (i.e. working through linkages) that were capable of controlling resources to obtain the response from KSPC. Resources (i.e. financial and social) and resource relationships affect the interrelationships between the actors of the project towards the observance of corporate social responsibility for these serve as mechanisms for leverage over the company.
Research Paper (Undergraduate, Bachelor of Arts in Political Science-Management) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Korea Electric Power Corporation-Salcon Power corporation (KSPC)